Thermal-hydrodynamic and exergetic study of two-phase flow in helically coiled pipe with helical wire insert. (February 2022) - Hashemian, Mehran; Jafarmadar, Samad; Ayed, Hamdi; Wae-hayee, Makatar
Abstract: This paper presents a multi-objective experimental study, to enhance the thermal performance of the helically coiled pipe. The main objective of this study is the hydrothermal evaluation of single-phase (water) flow and two-phase flow (air-water) transition through a helically coiled tube at the presence and absence of helically coiled wire. Water flow rate was varied from 2 l/min to 8 l/min and air flow rate was varied from 1 l/min to 5 l/min which makes the volume fraction (VF) range of 0.110–0.714. Thermal-frictional and exergetic behavior of two-phase flow for a helically coiled tube with a helical wire insert have been studied. Results show that in exergy efficiency inside helical tube without turbulator for single-phase flow is 87% higher than when the turbulator is inserted. The second law analysis demonstrated that the exergetic efficiency decreases by the increment of VF and water flow rate. Generally, when pressure drop increment is less important than heat transfer augmentation, simultaneous use of two-phase flow and turbulator is recommended. Conversely, single-phase flow with turbulator is recommended when the desired pressure drop is low.